Evaluation of Residues in Hen Eggs After Exposure of Laying Hens to Water Containing Per‐ and Polyfluoroalkyl Substances. (8th June 2020) - Wilson, Timothy B.; Stevenson, Gavin; Crough, Robert; de Araujo, Jesuina; Fernando, Nilhan; Anwar, Arif; Scott, Tyrone; Quinteros, José A.; Scott, Peter C.; Archer, Michael J.G.
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) have been used in aqueous film‐forming foams used in firefighting, resulting in soil and groundwater contamination and leading to human exposure via animal products grown in contaminated areas. The present study reports the relationship between PFAS intake by hens and the PFAS concentrations in the edible parts of eggs. Laying hens were exposed via drinking water to different concentrations of 4 PFAS compounds (perfluorooctane sulfonate [PFOS], perfluorohexane sulfonate [PFHxS], perfluorooctanoic acid [PFOA], and perfluorohexanoic acid) over 61 d. Egg PFAS residues were assessed for a further 30 d after exposure ceased. The target concentrations of PFAS were 0, 0.3, 3, 30, and 300 µg/L for the treatment groups T1–T5, respectively; and PFAS residues were determined from the eggs collected every second day. There was a linear correlation between the PFAS concentrations in the drinking water of hens and those detected in the egg, which could be useful in estimating PFAS concentrations in the egg by measuring water concentrations. Exposure of hens to drinking water with PFAS concentrations below the Australian Government Department of Health limits (PFOS and PFHxS, 0.07 µg/L; PFOA, 0.56 µg/L), and with no other sources of PFAS exposure, is unlikely to result in egg PFAS concentrations that would exceed the 10% limit set by Food Standards Australia New Zealand for human consumption. Environ Toxicol Chem 2021;40:735–743. © 2020 SETAC